E2.2 Paired learning – bringing clinicians and managers together in great ormond street hospital. (4th October 2017) - Dimitriades, K; Parish, E; Sharma, S
Abstract : Background: The paired learning programme originated in Imperial College in 2010. In 2015 it was piloted in critical care at GOSH in preparation for a pan-hospital run from January to July 2017. The aims of this program include the encouragement of cross boundary collaboration between clinicians and managers through project creation and organisational development. Methods: Twelve pairs of clinicians (registrar and above) and managers (Band 7 and above) were selected from across the hospital and matched to mix departments as well as Myers-Briggs type indicators (MBTI). Pairs were allocated both a senior clinical and executive supervisor. The programme consisted of monthly workshops, work shadowing, supervision meetings, peer mentoring and an improvement project. Results: The programme and the participants underwent multiple levels of evaluation. The participants evaluated each workshop for relevance and content with favourable results. Pre and post programme 'readiness to lead' questionnaires were used to evaluate progress. The projects ranged from service development to quality improvement and educational projects Conclusions: The greatest strength of this programme lies in its ability to encourage communication between participants. Techniques used included discussions around MBTI and appreciative inquiry which encourage peer learning. This backbone of communication is laid out early in the programme followed by workshops to assist in the management of their projects. Paired Learning can be used as an effective tool to break down barriers between clinicians and non-clinicians, fostering understanding and assisting in the creation of a collaborative working environment, whilst maximising the strengths of each profession. Key to its success is opening the lines of communication from the first session. The future success of organisations relies on their ability to break down silos, create networks and work collaboratively. The paired learning programme can be used to teach skills and encourage professionals to learn from one another. Senior supervision and project management assist in consolidating learning.